(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Metal complexes of antibiotics have shown promising antimicrobial activities against some resistant strain of bacteria by inhibiting the growth or killing the microorganisms. This phenomenon has lot of impact when the pathogenic microorganisms develop continuous resistance to the available antibiotics via various cellular defense mechanisms. Therefore, the search for alternative drug-molecules is of prime importance to combat antimicrobial resistance microorganisms. Antibiotic complexes with metal ions have attracted the attention of scientists looking for new drugs and to increase the activity of currently available antibiotics. The bioactivity of antibiotics can be improved by coordination of metal ions. To do so, cobalt(II) complexes of different antibiotics have been prepared from reaction of cobalt(II) nitrate with the antibiotics viz. amoxicillin, cefpodoxime proxetil (CFP), gatifloxacin, metronidazole, sulfamethoxazole, ketoconazole and levofloxacin. The synthesized compounds were characterized by TLC, solubility testing, melting point determination, UV-spectrophotometry and FTIR analysis. The compounds were screened for antibacterial activity against Bacillus cereus, Pseudomonas aeruginosa, Salmonella typhi, Staphylococcus aureus, Escherichia coli and Salmonella abony, and it was found that the synthesized complexes exhibited potent antibacterial activity. Bangladesh Pharmaceutical Journal 28(1): 11-19, 2025 (January)